Research on Optimization of TRIZ Application Driven by Design Needs and Targets - Liu, Wei; Cao, Guozhong; Tan, Runhua (Procedia CIRP, 2016)
The algorithm for inventive problem solving (ARIZ) provides methods and routes for designers in practical product design. However, ARIZ is a higher skill demanding large amount of professional knowledge for ordinary designers whose design skill were restricted by their insufficient professional knowledge and personal experience. To promote the efficiency of design work, this thesis provides a renovated application tactics for theory of innovative problem solving (TRIZ) which emphasize on differences existed in design needs and targets. Its main feature is based on one characteristic in application of TRIZ in practical design where different TRIZ tools may have different instructive effects on the problems belonging to different design types. In other words, the designers can choose the most suitable tool from toolkit of TRIZ to solve a certain design problem, the provided tactic with a workflow is able to help designers locate the promising TRIZ tools in accordance with design problems. The workflow contains several steps: Firstly, analyze the cognitive process of designers; secondly, propose an application method which is based on ontology to analyze innovative design problems; thirdly, utilize a mapping method between design problems’ targets and needs with certain TRIZ tools to help designers locate the suitable tools to solve design problems. Presenting two sample design examples to verify the practicability of optimized method proposed in last part of article.